Discovering Rhetorical Strategies in the Islamic Discourse of Tuan Guru Bajang Muhammad Zainul Majdi - Muhammad Rifqi Subakti Bahtiar; Hishamuddin Salim; Ari Safar Wadi (ITScience (Information Technology and Science), 2022)
A leader is prevalently a communicator in an organization, no matter the rule. A good leader typically has good communication skills, which allow them to elicit participation from the people they oversee. In particular, Muslim scholars are also pioneers of social and religious growth. Thus, competent communication efficiency is essential for them to lead people to a better way of life by part of Allah SWT. However, it is still found vast of Muslim scholars, which is uneven Islamic teaching presentation quality. Thus, the goal of this study is to come up with a decent speech that anaesthetizes the audience. This was accomplished by examining the use of hidden rhetoric in the address of TGB. Muhammad Zainul Majdi, the best Indonesian preacher in 2021. As a result, this qualitative study uses discourse analysis to examine his two speeches as samples and data sources. The result indicated that TGB. Muhammad Zainul Majdi applied a variety of hidden rhetorical techniques. In his Safari Da'wah Nusantara and national addresses, Muhammad Zainul Majdi used similitude, reverence, expertise, intelligence, and goodwill to demonstrate credibility or ethos and persuade the audience. Love or friendship versus hatred, Fear versus Confidence, Indignation versus Pity, and Admiration versus Envy are some of the pathos he uses. In terms of logos, He deals with three issues: parables, enthymeme, and data.